APPLICATION EFFECT BLEND KEPAYANG SEED AND CELERY THE QUALITY OF BEEF AT ROOM TEMPERATURE STORAGE - Sri Aprillianti, Permata Ika Hidayati, Tri Ida Wahyu Kustyorini (Jurnal Sains Peternakan, 2016)
ABTRACT This study aimed to determine the effect of kepayang seed and celery on the characteristics of microbiological, chemical, physical and beef fillet with a variety of shelf life. The material used in this study, namely beef, kepayang seed and celery. Method of research done at the Experimental experiment using completely randomized design (CRD), which consists of 4 treatments, Po: 0 hours, P1: 24 hours, P2: 36 hours, P3: 72 hours. With each treatment was repeated three times. he research variables including the Total Plate Count (TPC), protein testing, organoleptic. Analysis of data using a single anava if there is a difference then continued with Duncan test. Organoleptic analysis using the Kruskal Wallis test. The results showed that the preservation of the beef with the addition of celery seeds and with variation kepayang shelf life provides very significant influence (P˂0,01) against TPC and protein testing, with a low TPC values at 24 hours storage time is equal to 246.7 cfu / g and the value of the highest protein levels at 72 hours of storage that is equal to 16.83%. In the organoleptic tests give very significant influence (P 0.01). The results of research carried out can be concluded that in the long storage time of 24 hours of application kepayang and celery seed blend provides the best quality beef quality associated total microbial contamination. While the storage time of 72 hours gives the highest preference level panelist on the flavor of beef. Suggested for further research to test the fat content, pH, water and using other types of meat. Keywords : seed kepayang, celery, total plate count, organoleptic, protein